2022
DOI: 10.1088/1755-1315/1038/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Study of the use of Binahong (Anredera cordifolia) herbal as complementary treatment wounds in the Tenger Tribe

Abstract: The event of injury in indonesia is an increasing where this is dominated by blucits/brumes. One of their wound healing can be done with complementary therapy. Complementary therapy currently used by the tenger tribe in the treatment of daily wounds. This is because medicine plants are very easy to get in the tenger area.. The purpose of this study was to analyze the implementation of wound treatment carried out by the Tengger Tribe. The design used is a qualitative research with in-depth data collection descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several studies have shown that different parts of the Binahong plant can be used as a complementary therapy for treating injuries, burns, and scratches. The reported components responsible for aiding in the healing of various types of wounds include flavonoids, polyphenols, saponins, alkaloids, oleanolic acid, proteins, and ascorbic acid [18,32]. Both Binahong leaves and roots can be employed for wound healing.…”
Section: Wound Healermentioning
confidence: 99%
“…Several studies have shown that different parts of the Binahong plant can be used as a complementary therapy for treating injuries, burns, and scratches. The reported components responsible for aiding in the healing of various types of wounds include flavonoids, polyphenols, saponins, alkaloids, oleanolic acid, proteins, and ascorbic acid [18,32]. Both Binahong leaves and roots can be employed for wound healing.…”
Section: Wound Healermentioning
confidence: 99%